Age-Related Changes in Stand Structure, Spatial Patterns, and Soil Physicochemical Properties in Michelia macclurei Plantations of South China - Jiaman Yang; Jianbo Fang; Dehao Lu; Cheng Li; Xiaomai Shuai; Fenglin Zheng; Honyue Chen (Life)
Michelia macclurei, a valuable native broad-leaved species with good ecological and economic benefits and a key afforestation tree in South China, is facing progressive stand degradation and soil fertility decline with age. To investigate age-dependent dynamics of stand structure and soil properties, this study examined five stands (5, 10, 15, 20, and 42 a) in Yunfu City, Guangdong Province. The results revealed that (1) spatial distribution shifted from aggregated in young stands (5–10 a) to random in mature stands (42 a), with diameter and height class distributions becoming more diverse with age. Notably, topsoil (0–20 cm) in near-mature stands (15–20 a) exhibited not only significantly higher capillary porosity, non-capillary porosity, and water-holding capacity compared to young stands but also increased bulk density, indicating soil physical degradation. (2) Soil nutrient decline was observed in over-mature stands (42 a), characterized by a reduction in soil total nitrogen to 1.08 ± 0.06 g·kg−1 and total phosphorus to 0.16 ± 0.02 g·kg−1 in the topsoil (0–20 cm layer), suggesting age-related soil nutrient degradation. (3) Correlation analysis revealed a significant negative correlation between total potassium content and crown uniformity indices (p < 0.01), while available phosphorus was significantly positively correlated with crown and tree growth (p < 0.05). These findings provide critical insights for developing stage-specific management strategies in Michelia macclurei plantations.